CONCENTRATION OF TOBACCO MARKET: EVIDENCE FROM SERBIA - Vuković, Bojana; Mijić, Kristina; Spahić, Nataša (Economics of Agriculture, 2015)
This paper presents a research on market concentration of tobacco producers in the Republic of Serbia during 2010-2013. Market concentration was measured by Herfndahl Hirschman index (HHI) and Concentration index (CRn) based on independent variables: operating revenue, net earnings, equity and number of employees. The research of market concentration of tobacco producers based on operating revenue as the most referential variable indicated that the market of tobacco producers in the Republic of Serbia was highly concentrated and that it was an oligopoly. Leading companies dominated in the terms of the value of realized net earnings, equity and number of employees. Although leading companies had dominance in market share of Serbia, they had worse operating results in terms of effectiveness, structure of assets and fnancial performance in observed period.